OXPHOS Supercomplexes as a Hallmark of the Mitochondrial Phenotype of Adipogenic Differentiated Human MSCs - Hofmann, Andreas D.; Beyer, Mandy; Krause-Buchholz, Udo; Wobus, Manja; Bornhäuser, Martin; Rödel, Gerhard (PLOS ONE, 2012)
Mitochondria are essential organelles with multiple functions, especially in energy metabolism. Recently, an increasing number of data has highlighted the role of mitochondria for cellular differentiation processes. Metabolic differences between stem cells and mature derivatives require an adaptation of mitochondrial function during differentiation. In this study we investigated alterations of the mitochondrial phenotype of human mesenchymal stem cells undergoing adipogenic differentiation. Maturation of adipocytes is accompanied by mitochondrial biogenesis and an increase of oxidative metabolism. Adaptation of the mt phenotype during differentiation is reflected by changes in the distribution of the mitochondrial network as well as marked alterations of gene expression and organization of the oxidative phosphorylation system (OXPHOS). Distinct differences in the supramolecular organization forms of cytochrome c oxidase (COX) were detected using 2D blue native (BN)-PAGE analysis. Most remarkably we observed a significant increase in the abundance of OXPHOS supercomplexes in mitochondria, emphasizing the change of the mitochondrial phenotype during adipogenic differentiation.